Oral Rehabilitation of Patients Sustaining Orofacial Injuries: The UPenn Initiative. (November 2019) - Zhang, Q.Z.; Chen, C.; Chang, M.B.; Shanti, R.M.; Cannady, S.B.; O'Malley, B.W.; Shi, S.; Le, A.D.
Tissue injuries in the oral and maxillofacial structures secondary to trauma, warfare, ablative cancer, and benign tumor surgery result in significant losses of speech, masticatory and swallowing functions, aesthetic deformities, and overall psychological stressors and compromise. Optimal oral rehabilitation remains a formidable challenge and an unmet clinical need due to the influence of multiple factors related to the physiologic limitations of tissue repair, the lack of site and function-specific donor tissues and constructs, and an integrated team of multidisciplinary professionals. The advancements in stem cell biology, biomaterial science, and tissue engineering technologies, particularly the 3-dimensional bioprinting technology, together with digital imaging and computer-aided design and manufacturing technologies, have paved the path for personalized/precision regenerative medicine. At the University of Pennsylvania, we have launched the initiative to integrate multidisciplinary health professionals and translational/clinical scientists in medicine, dentistry, stem cell biology, tissue engineering, and regenerative medicine to develop a comprehensive, patient-centered approach for precision and personalized reconstruction, as well as oral rehabilitation of patients sustaining orofacial tissue injuries and defects, especially oral cancer patients.